Primary Hodgkin’s lymphoma of the middle ear: A rare cause of facial nerve palsy - Maithrea, N.; Periyathamby, S.; Mohamad, Irfan (Elsevier, 2017)
Facial nerve palsy can occur whenever any part of the facial nerve is affected. It can be complete or partial, unilateral or bilateral and upper motor or lower motor neurone type. Common causes of unilateral lower motor neuron facial nerve palsy include trauma, infections of the middle ear, neoplasms of the parotid, iatrogenic and idiopathic. Hodgkin lymphoma typically presents with an asymptomatic lymphadenopathy, but associated symptoms include constitutional symptoms, intermittent fever, chest pain, or shortness of breath. We present an extremely rare case of facial nerve palsy secondary to primary classical nodular sclerosis Hodgkin’s lymphoma, arising from the left middle ear extending into the external auditory canal.